Penerapan Metode Pembelajaran Deskriptif untuk Meningkatkan Motivasi Belajar Siswa SMP pada Mata Pelajaran Pendidikan Agama Islam - Siti Lestari (Jurnal Indonesia Kajian Pendidikan Islam, 2026)
Background: Student learning motivation is a crucial factor in achieving successful Islamic Religious Education (IRE) learning outcomes. However, low learning motivation remains a challenge, as classroom instruction is often teacher-centred and offers limited opportunities for active student engagement. Objective: This study aimed to examine the implementation of the descriptive learning method in improving students’ learning motivation in Islamic Religious Education at SMP Negeri 22 Mukomuko. Method: The study employed Classroom Action Research (CAR), conducted in three cycles: planning, action, observation, and reflection. Data were collected through observations, interviews, tests, and documentation and were analysed descriptively. Results: The findings indicated a continuous improvement in students’ learning motivation across the three cycles. The average motivation score increased from 62% in Cycle I to 76% in Cycle II and reached 88% in Cycle III. Improvements were observed in students’ attention, participation, confidence in expressing opinions, involvement in discussions, and enthusiasm for learning. Conclusion: The descriptive learning method effectively enhanced students’ motivation to learn in Islamic Religious Education. Contribution: This study contributes to the development of more active, interactive, and student-centred learning practices in Islamic Religious Education.